Factors Influencing the Use of Control Measures to Reduce Occupational Exposure to Welding Fume in Australia: A Qualitative Study - Renee N. Carey; Lin Fritschi; Ha Nguyen; Kamil Abdallah; Timothy R. Driscoll (Elsevier, 2023)
Background: Exposure to welding fume is associated with adverse effects on worker health. The use of various control measures can reduce levels of exposure and the resulting health effects. However, little is known about the factors that may influence workers' use of control measures in the workplace and their perceived intervention needs. This study aimed to investigate workers' and other stakeholders' views on ways to improve the use of welding fume control measures in Australian workplaces. Methods: We conducted a series of online focus group discussions and individual interviews with participants who have some occupational involvement in welding, whether as workers, employers or industry representatives, union representatives, or regulators. A semi-structured question guide was used, and all discussions and interviews were recorded and transcribed for analysis. Results: Five focus group discussions and five individual interviews were conducted with a total of 21 participants. Three major themes emerged. The first addressed the current awareness of welding fume harms and concern about exposure; the second focussed on the current use of control measures, and barriers and facilitators to their use; and the last centred around intervention needs and the contents of a potential effective intervention. Conclusion: Improving the use of control measures to prevent exposure to welding fume requires knowledge around the barriers and facilitators of control, use, and the intervention needs of stakeholders. This study has provided such knowledge, which will facilitate the design and implementation of an intervention to reduce welding fume exposure and ultimately protect the health of workers.